Tiempo y dinero en el encuentro psicoanalítico (2009)
ABSTRACT: The issue of money in the analytical setting, as payment, remains in the shade, or it is left to each analyst´s discretion. The same situation is seen regarding duration of session. This article tries to clearly explain this subject by using analytical arguments and historical references.